Preface: 3rd International Conference on Artificial Intelligence and Communication Technology (AICT 2024) - Zhong, Wei; Shi, Jun; Thompson, Herman (Transactions on Computer Science and Intelligent Systems Research, 2024)
The organizing Committee of AICT 2024 was proud to present the proceedings of the 3rd International Conference on Artificial Intelligence and Communication Technology (AICT 2024), which was held on August 17-18, 2024 in Chongqing, China.The aim as well as objective of this AICT is to present the latest research and results of scientists related to Artificial Intelligence, Communication Technology and related topics. This conference provides opportunities for the delegates to exchange new ideas face-to-face, to establish business or research relations as well as to find global partners for future collaborations. We hope that the conference results will lead to significant contributions to the knowledge in these up-to-date scientific fields.All full paper submissions to the AICT 2024 must be written in English, and will be sent to 2-4 reviewers and evaluated based on originality, technical or research content, correctness, relevance to conference, contributions, and readability. The full paper submissions will be chosen based on technical merit, interest, applicability, and how well they fit a coherent and balanced technical program.This AICT conference has received 96 manuscripts. And less than half of the submissions were accepted by our reviewers and the press. By submitting a paper to this AICT conference, the authors agree to the review process and understand that papers undergo a peer-review process. Manuscripts will be reviewed by appropriately qualified experts in the field selected by the Conference Committee, who will give detailed comments and-if the submission gets accepted-the authors submit a revised version that takes into account this feedback. All papers are reviewed using a double-blind review process: authors declare their names and affiliations in the manuscript for the reviewers to see, but reviewers do not know each other's identities, nor do the authors receive information about who has reviewed their manuscript. The Committees of this 3rd AICT invest great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit.Hopefully, all participants and other interested readers benefit scientifically from the proceedings and also find it stimulating in the process.With our warmest regards,Wei Zhong, Jun Shi, Herman ThompsonConference Organizing Committee